Determinants of entrepreneurial intentions among postgraduate students: evidence from a University in the Eastern Cape - Chagi, Ntomboxolo Girlie; Ncanywa, Thobeka; Asaleye, Abiola John (Frontiers in Education, 2025)
IntroductionEntrepreneurship plays an important role in driving innovation, job creation, and economic sustainability, particularly in an under-resourced environment such as South Africa’s Eastern Cape.MethodsThis study investigates the factors influencing the development of entrepreneurial mindset, identity, and self-efficacy among postgraduate students, drawing on the integrated theoretical perspectives of the Theory of Planned Behavior (TPB), Social Cognitive Theory (SCT), and Human Capital Theory (HCT). Adopting a qualitative case study approach, data were collected through 24 semi-structured interviews with postgraduate students, lecturers, and university managers at a public university in the region.ResultsThe findings reveal that entrepreneurship education promotes a shift in perception from a transactional, business-oriented view of entrepreneurship to a mindset characterized by innovation and strategic problem-solving. Experiential learning and mentorship were identified as enablers of self-efficacy and entrepreneurial identity, aligning with SCT’s emphasis on social modeling and mastery experiences.DiscussionHowever, structural barriers such as limited access to practical training, inadequate funding, and unsupportive institutional policies were found to weaken students’ perceived behavioral control, as framed by TPB. While participants acknowledged the value of skill acquisition for personal and economic advancement, the return on human capital was constrained by resource gaps. The study stresses the need for contextually grounded entrepreneurship education, integrated mentorship frameworks, and institutional reform to create an enabling environment that supports student entrepreneurship in disadvantaged communities.